Upaya Peningkatan Omset Penjualan UMKM melalui Penerapan Digital Marketing terhadap UMKM di Bekasi - Ery Teguh Prasetyo; Istianingsih Sastrodiharjo; Robertus Suraji (Jurnal Pemberdayaan Umat, 2022)
Purpose: To increase knowledge and digital marketing skills to increase MSME sales turnover. Research Methods: providing training in the form of lectures and creating digital media business accounts and managing media to market products. Results: Changes in participants' understanding of the importance of digital marketing as an effort to increase sales turnover, skills in creating business accounts, managing them, and increasing business motivation. Limitations: This activity has not been able to achieve the ideal target, there are limited time for implementation and the funds available for the activity. Contribution: The application of digital marketing by MSME actors in the village of Kedung Supervisor provides positive benefits for increasing sales turnover.